Platforms for quantum information and technology - Cardoso, Fernando Redivo (Universidade Federal de São Carlos, 2024)
This work presents a collection of scientific research results in the field of quantum information. The first paper describes the mathematical properties of a particular type of state of light, called the two-mode squeezed state (TMSS). We have shown that it is possible to generate a superposition of such states with particular probability distributions, making them suitable for applications in quantum information. In particular, such states are effectively phase insensitive, a property that enables a larger extraction of information regarding a dynamical process. The second paper deals with an extensive discussion on the complexity of quantum algorithms. It was observed that while quantum algorithms can, under certain conditions, outperform classical algorithms in time or space complexity, some key steps such as state preparation and information retrieval are not always taken into account when analysing the complexity of quantum algorithms. For this reason, the aim of this study was to provide a complete complexity analysis for the implementation of quantum algorithms, considering different alternatives in terms of state preparation, quantum gate implementation and measurement techniques. We provide an asymptotic analysis of different algorithm implementation strategies. Finally, the last paper deals with the Hong-Ou-Mandel interference visibility of photons emitted in a cascade process. As a result of a two-photon excitation process, an entangled photon pair is emitted. This unwanted entanglement affects the coherence of the reduced single photon state, i.e. one of the photons emitted in the cascade process. As a result, the visibility of the Hong-Ou-Mandel interference is reduced. We show that, under certain conditions, it is possible to circumvent the restriction imposed by the time-energy entanglement by applying a post-selection method. The experimental results together with the theoretical framework are presented to provide a complete analysis of the method.
Platforms for quantum information and technology
Keywords: Quantum computation; Quantum information; Quantum interference; Computação quântica; Informação quântica; Interferência quântica; CIENCIAS EXATAS E DA TERRA::FISICA